When is escalation of commitment unstoppable in group settings? An iterative economic modeling approach to unveil the dark side of group decision‐making. (30th July 2020) - Montecinos‐Pearce, Alejandro; Rodrigo, Pablo; Duran, Ignacio J.
Abstract : Escalation of commitment (EOC) has been usually studied from a psychological lens, and only recently have scholars approached EOC from an economic perspective. We contribute to this by focusing on iterative decision‐making in group settings with a game theory approach. We study how the group members' strategic interaction may result in continuing failing courses of action. Drawing on the Byzantine generals' problem, our model considers an iterative decision‐making process where committee participants vote based on private information to escalate or not. Our article demonstrates that if decision‐makers reset their beliefs based on the committee's previous decision, then EOC becomes perpetual.